Heterosis Exploiting Breeding Schemes for Rapid Yield Enhancement - International Potato Center (2014)
During SASHA Phase 1, clear evidence was generated for the first time that heterosis can be successfully exploited in sweetpotato for significant yield gains for roots and foliage. There is high potential for application to other root and tuber and banana crops, with more efficient breeding helping to solve the problem of feeding the ever growing population.